Tingkat Konsumsi Zn, Se dan GDS Pasien Diabetes Melitus Tipe II - Adinda, Shintya Permata; Luthfiyah, Fifi (NUTRITURE JOURNAL; Vol 2 No 3 (2023): Nutriture Journal, 2023)
Background: : According to 2019 WHO data, 7 out of 10 main causes of death in 2019 were non-communicable diseases. Diabetes has become one of the main causes of death (WHO 2020). In 2019 there were around 463 million adults living with Diabetes Mellitus worldwide and as many as 90-95% had Type II DM (IDF 2019). Based on the 2018 (Riskesdas) results, the national prevalence of type II DM reached 8.5% of the total population. A total of 12 provinces have DM prevalence above the national prevalence, namely East Java province (Riskesdas 2018). In the city of Batu, type II DM is one of the 10 most common diseases, namely 4,329 people (Central Statistics Agency for Batu City 2018). Management of type II DM includes 6 pillars, one of which is medical nutrition therapy. This principle requires 3J orderliness. Based on the type, nutrients are divided into 2. The minerals Zinc and Selenium are examples of micronutrients. This mineral includes metalloenzyme minerals which work as antioxidants, so they have the potential to prevent degenerative diseases (Ozenc et al., 2015) in (Yuliati Widiastuti 2016). Objective: To determine the level of Zn and Se consumption in type II DM patients treated at RSU Karsa Husada Batu. Design: Descriptive Observational using incidental sampling. Results: Nine type II DM patients were collected with severe deficits in Zn consumption, normal Se and high GDS levels Conclusions: A deficit level of Zn consumption influences the results of higher GDS levels, whereas an excessive level of Se consumption accompanied by normal Zn can produce GDS levels that are close to normal. Keywords : Diabetes Mellitus type II; Selenium; Zinc.